Axial performance of GFRP composite bars and spirals in circular hollow concrete columns. (February 2021) - Raza, Ali; Ali, Babar; Masood, Bilal; ur Rehman, Anees
Abstract: The fiber reinforced polymer (FRP) bars are used in hollow concrete columns (HCCs) to alleviate the steel-reinforcement corrosion problem and to make an efficient and lightweight structure. The presented study has endeavored to numerically and theoretically explore the structural behavior of hollow concrete columns (HCCs) reinforced with glass fiber reinforced polymer (GFRP) bars and spirals. Six HCCs were simulated in a commercial finite element software ABAQUS 6.14. The control finite element model (FEM) was calibrated for various variables of HCCs using the previous experimental testing results. The complex nonlinear behavior of concrete was defined using the concrete damaged plastic model (CDPM) and the behavior of GFRP bars was considered as linear elastic. The proposed FEM portrayed a close correlation with the testing results of HCCs. Moreover, the different empirical models were proposed for predicting the two-peak loading behavior of FRP-reinforced HCCs based on a large database constructed from the previous research.